1983
DOI: 10.1128/aac.24.5.803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (E)-5-(2-bromovinyl)-2'-deoxyuridine on proliferation of human fibroblasts, peripheral blood mononuclear cells, and granulocyte-monocyte progenitor cells in vitro

Abstract: Inhibition of human fibroblasts, granulocyte-monocyte progenitor cells, and lymphocytes was observed at (E)-5-(2-bromovinyl)-2'-deoxyuridine concentrations ranging from 21 to 197 p.g/ml. These concentrations were 10-to 100-fold above usual serum concentrations after oral administration. (E)-5-(2-Bromovinyl)-2'-deoxyuridine compares favorably with currently used antivirals in terms of in vitro myelotoxicity and immunotoxicity.(E) -5 -(2-Bromovinyl)-2' -deoxyuridine (BVdU) is a synthetic pyrimidine deoxynucleosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…As an inhibitor of virus replication, we decided to employ (E)-5-(2-bromovinyI)-2'-deoxyuridine (BVDU) which had been successfully utilized to develop an efficient in vitro lat ency system in human embryo lung (HEL) cells [3], In agreement with the recent obser vation of Bubley et al [4], both the TK and T K + (HSV-1) L cell sublines (LTK and LTK+) were found to be highly susceptible to the toxic effects of BVDU at concentrations 100-1,000 times lower than those tolerated by other cell systems [5,6], This prompted us to select BVDU-resistant cell lines from both LTK and LTK+ cells. These cell lines would answer the questions of the mode of action of BVDU in the naturally susceptible cell lines and of the effects of BVDU on L cells carry ing the HSV-TK gene.…”
supporting
confidence: 54%
“…As an inhibitor of virus replication, we decided to employ (E)-5-(2-bromovinyI)-2'-deoxyuridine (BVDU) which had been successfully utilized to develop an efficient in vitro lat ency system in human embryo lung (HEL) cells [3], In agreement with the recent obser vation of Bubley et al [4], both the TK and T K + (HSV-1) L cell sublines (LTK and LTK+) were found to be highly susceptible to the toxic effects of BVDU at concentrations 100-1,000 times lower than those tolerated by other cell systems [5,6], This prompted us to select BVDU-resistant cell lines from both LTK and LTK+ cells. These cell lines would answer the questions of the mode of action of BVDU in the naturally susceptible cell lines and of the effects of BVDU on L cells carry ing the HSV-TK gene.…”
supporting
confidence: 54%
“…killer (K) cell or natural killer (NK) cell activities or proliferative responses to mitogens or specific antigens, unless it is present at high or very high concentrations (40-200 pg/ml) [34,35], that is 20000-100000-fold higher than its minimum inhibitory concentration for VZV [26].…”
Section: Resultsmentioning
confidence: 99%